2022
DOI: 10.5603/fm.a2021.0087
|View full text |Cite
|
Sign up to set email alerts
|

Acromion types and morphometric evaluation of painful shoulders

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As the acromion curves, the contact area became more like a point than a line, thus making the tear more likely to be longitudinal. 26 The AI in the L‐shaped tear group was the highest of all four groups, although the LAA in the L‐shaped was the smallest. Interestingly, the horizontal group presented with completely opposing data when compared to the L‐shaped group.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As the acromion curves, the contact area became more like a point than a line, thus making the tear more likely to be longitudinal. 26 The AI in the L‐shaped tear group was the highest of all four groups, although the LAA in the L‐shaped was the smallest. Interestingly, the horizontal group presented with completely opposing data when compared to the L‐shaped group.…”
Section: Discussionmentioning
confidence: 85%
“…The AS in the longitudinal group was significantly larger than that in the horizontal group and the L‐shaped group. As the acromion curves, the contact area became more like a point than a line, thus making the tear more likely to be longitudinal 26 . The AI in the L‐shaped tear group was the highest of all four groups, although the LAA in the L‐shaped was the smallest.…”
Section: Discussionmentioning
confidence: 99%
“…It was emphasized that this situation is important in the formation of the acromion type [23]. Among the acromion types, especially the type 3 form, the acromio-humeral joint space is narrower [24]. Other studies have reported that individuals with type 3 acromion have more SIS symptoms [21,25].…”
Section: Demographic Characteristics Of the Individuals According Tomentioning
confidence: 99%